KELANGKAAN BAHAN BAKU UNTUK INDUSTRI PENGOLAHAN UDANG DI JAWA TIMUR - Adrian D. Lubis (Buletin Ilmiah Litbang Perdagangan, 2009)
Indonesia is one of a main shrimp producers in the world. But in last two years, some shrimp industries, especialy in East Java is  complained to raw material insufficiency, and continually require government to give permission to import. However, the government does not allow shrimp import to prevent the spread of white sport syndrome virus in Indonesia. The study found that the raw material scarcity is only happens in East Java. It also predct that Indonesia’s shrimp supply will increase in the future. The abundance of shrimp supply will make Indonesia is likely donot need shrimp import. However, some recomendation is needed for government to issue special policy in supply continuing in East Java.